Inovasi Guru Dalam Meningkatkan Minat Belajar Siswa Dalam Pembelajaran Visual Berbasis Poster Edukatif Di Sd Negeri 1 Bendo Pedan Klaten - christina Indriasari; Esti Ismawati; Tukiyo .; Hersulastuti . (CV. ITTC INDONESIA, 2025)
This study aims to describe teacher innovations in increasing student learning interest through educational poster-based visual learning in Indonesian language subjects. This study uses a qualitative approach with a descriptive research type. The study was conducted at SD Negeri 1 Bendo, Pedan District, Klaten Regency. Data collection techniques included non-participatory observation, semi-structured interviews, and documentation with the research subjects of the principal, Indonesian language teachers, and fifth-grade students. Data validity was tested through triangulation of sources and techniques. Data analysis was carried out through the stages of data condensation, data presentation, and drawing conclusions. The results of the study showed that teacher innovations were carried out by creating a pleasant learning atmosphere, linking the material to the context of everyday life, holding question and answer sessions, using various learning media, and adjusting the lesson plan to students' abilities. The use of educational poster-based visual media was able to increase student learning interest as shown through feelings of joy, interest, attention, and active involvement of students in Indonesian language learning.